Aktivitas Antimutagen Isoflavon Glikosida Hasil Transglikosilasi Enzimatik CGT-ase Bacillus macerans - Sulistyo, Joko; Soeka, Yati Sudaryati (Universitas Atma Jaya Yogyakarta, 2009)
It has been known that isoflavone have biological activities such as antioxidant, antibacteria, antimutagenesis, and anticancer. Isoflavone aglycone uses such as genistein, daidzein and glycitein are limited since they are unstable and uneasily to dissolve in water. Through enzymatic transglycosylation reaction, its stability and solubility could be improved. In this study, genistin (isoflavone glycoside) was synthesized from genistein (isoflavone aglycone) by application of transfer reaction using enzyme cyclodextrin glucanotransferase (CGT-ase) of Bacillus macerans. Identification of the product was determined by TLC with methanol: chloroform (1:3, v:v) as eluent. Rf value 0.75 of the synthesized product was close to the Rf value standard of authentic genistin glycoside. The synthesized genistin was furthermore assayed to determine its antimutagenesis activity according to the Ames methode on E. minimal glucose media had been precultured with a mutant strain of Salmonella thypimurium TA98. The tested bacterial strain was induced with aflatoksin B1 as mutagen which had been activated with a lever homogenate. The result showed that the solubility and some biological properties of the synthesized genistin were improved higher than that of genistein, while it was found to be lower than that of the commercial genistin.